Anti-quorum sensing and biofilm inhibitory effect of some medicinal plants against gram-negative bacterial pathogens: in vitro and in silico investigations. Issue 10 (October 2022) - Samreen,; Qais, Faizan Abul; Ahmad, Iqbal
Abstract: Multidrug resistance (MDR) in pathogenic bacteria have become a major clinical issue. Quorum sensing regulated bacterial virulence is a promising key drug target for MDR infections. Therefore, the aim of the present work was to assess the anti-quorum sensing properties of selected medicinal plants against bacterial pathogens as well in silico interaction of selected bioactive phytocompounds with QS and biofilm-associated proteins. Based on the ethnopharmacological usage, 18 plants were selected using methanolic extract against Chromobacterium violaceum 12472. The most active extract ( Acacia nilotica ) was fractionated in increasing polarity solvents (n-hexane, chloroform and ethyl acetate) and tested for anti-QS activity. The most active fraction i.e. ethyl acetate fraction was evaluated for their activity at sub-MICs against QS-associated virulence factors of Pseudomonas aeruginosa PAO1 and Serretia marcescens MTCC 97. Microtiter plate assay and light microscopy was used to determine inhibition of biofilm. Phytochemicals of the ethyl acetate fraction were analysed by GC/MS and LC/MS. Phytocompounds were docked with QS (LasI, LasR, CviR, and rhlR) and biofilm proteins (PilY1 and PilT) using Auto dock vina. The MIC of ethyl acetate fraction determined was 250, 500, and 1000 μg/ml against C. violaceum 12472, P. aeruginosa PAO1, and S. marcescens MTCC97 respectively. At sub-MICs QS regulated virulence factors production and inhibited biofilms broadly (more than 50 percent). GC/MS detected the major bioactive compound benzoic acid, 3, 4, 5-trihydroxy-, methyl ester (61.24 %) and LC-MS detected Retronecine for the first time in A. nilotica pods. In silico, dehydroabietic acid occupied the same cavity as its antagonist in the CviR ligand binding domain. Also, betulin and epicatechin gallate interact with biofilm proteins PilY1 and PilT, preventing biofilm formation. The findings suggest that the phytochemicals of A. nilotica pod could be exploited as an anti-QS agent against Gram-negative pathogens. To discover therapeutic efficacy of standardised bioactive extract/phytochemicals must be tested under in vivo condition. Abstract : Medicinal plant; Quorum sensing; Virulence factors; Biofilm inhibition; Phytochemistry.